Modelling on Shock-Induced Energy Release Behavior of Reactive Materials considering Mechanical-Thermal-Chemical Coupled Effect - Baoyue Guo; Kerong Ren; Zhibin Li; Rong Chen (Shock and Vibration)
Reactive material (RM) is a new type of energetic material, which is widely used in the military technology fields such as fragmentation warheads and shaped charge warheads. Violent chemical reactions take place in the impact process of reactive materials, and how to realize the macro numerical simulation of shock-induced energy release behavior of reactive materials is one of the most urgent problems to be solved for its future military applications. In this study, a numerical simulation approach and procedure is proposed, which can simulate the shock-induced energy release behavior of reactive materials on a macro scale. Firstly, program implementation of the mechanical-thermal-chemical coupled effect model for RM is realized in the second-development interface of LS-DYNA software. Then, the adaptive simulated annealing algorithm is used to fit the chemical reaction kinetic parameters of RM using the direct ballistics test data. Finally, the simulation calculation of the fragment penetrating upon steel plate is carried out to expand the applicability of the numerical simulation approach proposed in this study. The results show that the numerical simulation approach proposed in this study can reproduce the results of the direct ballistics test more accurately, which assumes practical significance for the engineering application of reactive materials in the military field in the future.